Strategies to Strengthen BUMDES Governance in Increasing Village Economic Independence Through Participatory Management Principles Case Study in Lembata Regency - Tri Suris Lestari; Christiana Wahyuningrum; Agatha Helena Deze; Agustina Sadri Yathy Lay (Universitas Veteran Bangun Nusantara Sukoharjo, 2026)
Strengthening the governance of Village-Owned Enterprises (BUMDes) is a strategic step in realizing village economic independence, but its implementation in various regions still faces challenges such as weak management capacity, lack of transparency, low community economic literacy, and dominance of top-down decision-making models. These problems can also be seen in the context of Lembata Regency which shows the gap between the ideals of participatory governance and the reality of its implementation in the field. This study aims to analyze strategies to strengthen the governance of BUMDes through the application of participatory management principles in order to increase village economic independence. The research method uses a qualitative approach with a case study design, through data collection techniques in the form of in-depth interviews, observations, and analysis of institutional documents. The results of the study show that efforts to strengthen the governance of BUMDes can be effective if supported by clear internal regulations, increasing the capacity of human resources, an open transparency mechanism, expanding community participation space, and the development of local potential-based business units. Meanwhile, the main obstacles lie in the hierarchical culture, limited human resources, and weak public reporting system. This study emphasizes that the strategy of strengthening participatory management-based governance is an important foundation for the realization of inclusive, accountable, and sustainable village economic institutions.